Analysis of the Thermal Elastohydrodynamic Lubrication Performance of Water-Lubricated Tenmat Bearing - Dong Ning; Wang Youqiang; Liu Qian; Huang Xingbao (Jixie chuandong)
The elastohydrodynamic lubrication numerical analysis of water-lubricated Tenmat bearing is carried out by using the Reynolds equation with thermal effect.The effects of load,speed and shaft diameter on the pressure and film thickness of Tenmat bearing water lubrication film are discussed by the numerical simulation.The results show that thermal effect has little effect on the pressure,but the film thickness decrease under the thermal condition.The pressure peak is increased greatly with the increase of load,but the film thickness is decreased.The pressure peak is decreased with the increase of speed,but the film thickness is increased.The influence of shaft diameter on the pressure is not obvious,but the film thickness is decreased with the increase of shaft diameter.